Penguatan Moderasi Beragama Generasi Milenial melalui Pembelajaran Sinoptik Berbasis Literasi di Era Industri 4.0 - Asep Encu; Momon Sudarma (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2024)
The millennial generation growing up in the digital era possesses unique characteristics in absorbing educational values, including in the context of religious moderation. This research aims to examine and develop a synoptic learning model based on literacy suitable for strengthening religious moderation among the millennial generation in the context of Industry 4.0. The method employed involves literature review and qualitative analysis to identify the effectiveness of synoptic learning integrating digital technology and information literacy. The findings indicate that a synoptic learning model incorporating digital literacy elements can enhance understanding and acceptance of religious moderation values among millennials. Learning is facilitated by presenting concise and relevant content, utilizing digital platforms familiar to this generation such as social media, interactive learning applications, and short videos. With this approach, millennials can become more actively engaged and critical in filtering and interpreting religious information they receive. This research implies that strengthening religious moderation can be achieved through adapting learning methods that resonate with the characteristics of the millennial generation. This literacy-based synoptic model is expected to serve as a guide in formulating effective religious education strategies in the Industry 4.0 era, while also serving as a concrete step in anticipating potential radicalism that may arise from misunderstandings of religious information.